Designing a smart construction work management system for improving the safety and productivity using wearable devices. (14th December 2021) - Choi, Young-Hwan; Woo, Mi-Sun; Lee, Seung-Hyun; Hong, Min
The main purpose of this research is to design a smart construction work management system for improving the productivity of construction operations and the workers' safety by using wearable smart devices. The proposed smart management system includes the development of smart safety helmets, watches, shoes, and applications to conveniently accumulate various construction field data in real-time. It can be applied to manage the construction workers' productivity and to improve their safety by providing a warning notification for abnormal situations. Also, it stores the data regarding construction workers' safety, physical states, and their construction work progress on to the server effectively by using a smartphone.